Preparation and evaluation of virus-like particle vaccine against H3N8 subtype equine influenza. (August 2021) - Zhang, Pengju; Sun, Yixue; Tan, Chengcheng; Ling, Mengmeng; Li, Xintao; Wang, Weixia; Cong, Yanlong
Abstract: To prevent and control H3N8 subtype equine influenza, we prepared virus-like particles (VLPs) comprising the HA, NA and M1 proteins of H3N8 equine influenza virus (EIV) through the insect cell-baculovirus expression system. The results of Western blot and hemagglutination analyses demonstrated that the constructed VLPs comprising HA, NA and M1 proteins have good hemagglutination activity. Immunoelectron microscope revealed that the VLPs share similar morphology and structure with natural virus particles. The hyperimmune serum from horses immunized with the VLPs were injected into mice by means of artificial passive immunization and then challenge, or challenge following by injecting hyperimmune serum. The results showed that the equine hyperimmune serum has good preventive and therapeutic efficacy against the infection of H3N8 EIV. The study provides a technical foundation for the development of H3N8 EIV VLP vaccine. Highlights: H3N8 EIV VLP vaccine was successfully constructed. H3N8 EIV VLPs share similar morphology and structure with natural virus particles. Hyperimmune serum has good preventive and therapeutic efficacy against the infection of H3N8 EIV.